Erythema Multiforme post-Orf viral infection: a comprehensive review of the literature with a case report highlight - Mona Alkallabi; Khalid Nabil Nagshabandi; Shaden Alobaid; Reem Bin Idris; Amany Fathaddin (PAGEPress Publications, 2024)
Orf, also known as ecthyma contagiosum, is a highly contagious zoonotic infection linked to direct contact with infected sheep, goats, or reindeer, posing a significant risk to farmers, veterinarians, shepherds, and butchers. This study presents a case of a 41-year-old female who developed Orf, complicated by the rare occurrence of Erythema Multiforme (EM), after handling sheep meat. The patient initially presented with a progressive painful skin eruption on the left dorsum of the little finger, which subsequently worsened and led to the development of generalized painful and itchy skin lesions, including target lesions typical of EM, on the palms, soles, and extremities. The diagnosis was confirmed through clinical examination and skin biopsy. The patient was treated with antihistamines and topical corticosteroids, resulting in a complete resolution of symptoms within three weeks. Our underscores the importance of recognizing EM as a potential complication of Orf infection, particularly in individuals with occupational exposure to animals.